Analisis Prospek Pertanian Dalam Mengembangkan Potensi Ekonomi Masyarakat Kelurahan Marawas Kecamatan Tondano Utara - John R. M. Apituley (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
Analysis of agricultural prospects is crucial for developing the economic potential of communities, especially in rural areas. Agriculture plays a strategic role in food security, employment, and increasing community income. This analysis helps identify superior commodities, market opportunities, and appropriate development strategies to improve the welfare of farmers and communities. Agriculture plays a central role in the Indonesian economy, particularly in subdistricts and rural areas. Analysis of agricultural prospects can help measure the level of public welfare and the potential of natural resources. Agricultural prospects are a crucial step in developing the economic potential of communities, especially in the regions. By understanding existing potential and opportunities, sustainable and farmerfriendly agricultural development can be implemented, thereby improving community welfare and driving regional economic growth.